Evaluation of Centrifugation Using 4% NaOH for Acid-Fast Bacilli Detection and Ziehl–Neelsen Smear Quality in Sputum Specimens with Negative Rapid Molecular Test Results - Sahfiya, Annisa Nazla; Mayasari, Ulfayani; Widiarti, Leni (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study aimed to evaluate the effect of centrifugation with 4% sodium hydroxide (NaOH) on acid-fast bacilli (AFB) detection using the Ziehl–Neelsen method in sputum specimens with negative Molecular Rapid Test (MRT) results. This laboratory-based experimental study employed a paired design involving 50 sputum specimens with negative MRT results. Each specimen was examined using the Ziehl–Neelsen method before and after centrifugation with 4% NaOH. The primary outcome was the change in AFB detection results, while smear appearance was descriptively assessed based on background clarity and the presence of debris. All specimens (50/50; 100%) remained AFB-negative both before and after centrifugation, indicating that centrifugation with 4% NaOH did not alter AFB detection outcomes. Descriptively, centrifuged smears showed cleaner backgrounds and less debris, which facilitated microscopic examination; however, smear quality was not evaluated using a quantitative scoring system. Therefore, centrifugation with 4% NaOH did not improve AFB detection by the Ziehl–Neelsen method in sputum specimens with negative MRT results. Nevertheless, centrifuged smears appeared visually cleaner during microscopic examination, suggesting a potential benefit for specimen preparation that requires further validation using standardized quantitative assessment.